Lifestyle, efficiency & limits: modelling transport energy and emissions using a socio-technical approach - Brand, C; Morton, C; Anable, J (European Council for an Energy Efficient Economy, 2017)
The Paris climate change agreement and ‘dieselgate’ emissions scandal in the US have prompted policy makers, regulators and industry to re-evaluate strategies to meet climate change mitigation and air quality goals. While a wide range of supply and demand policies have been proposed at both national and subnational/local levels, implementation and even the supporting research evidence have been lagging ambition in many parts of the world. It is well known that societal transport energy consumption and related emissions are influenced by technical efficiency, the carbon/pollutant content of energy and by ‘lifestyles’ and socio-cultural factors. However, only a few attempts have been made to operationalise these insights into models of future transport energy demand or even scenario analysis. In particular, insights into human behaviour, lifestyle change and the important role of individual attitudes and perceptions are often overlooked by policy makers. This paper addresses this gap in research and practice by presenting a quantitative scenario exercise using an integrated transport-energy-environment systems model to explore four contrasting futures for Scotland that compare ‘lifestyle’ change and socio-cultural factors against a low carbon technology focussed transition pathway using a socio-technical approach. We found that radical demand and supply strategies can have important synergies (and potential trade-offs) between reducing life cycle greenhouse gas and air quality emissions. Lifestyle change alone (without an EV transition) has a similar effect on transport carbon and air quality emissions than a transition to EVs with no lifestyle change. Yet both have limits to meeting future targets, which may only be achieved with a combined strategy of radical change in travel patterns, mode choice, vehicle occupancy and on-road driving behaviour with high electrification and phasing out of conventional petrol and diesel road vehicles.